Effect of intermittent water stress on oil quality in groundnut (Arachis hypogaea L.): Effect of intermittent water stress on oil quality in groundnut (Arachis hypogaea L.) - P SRIVALLI; H L NADAF (Journal of Oilseeds Research, 2020)
An RIL population generated from the cross TMV-2 × GM 6-1 was evaluated by imposing intermittent water stress during post-flowering crop growth of consecutive seasons of summer 2013 and 2014 at the UAS, Dharwad. Intermittent water stress had positive effect and mean of traits increased for oleic acid content, oleic to linoleic acid ratio. Moderate GCV, PCV, high heritability together with moderate to high GAM were noticed for oleic acid, linoleic acid, oleic/linoleic acid ratio indicating less influence of environment and ample scope in selection of these traits.